Fungi associated with table grape propagation material, with emphasis on Neoscytalidium dimidiatum and Quambalaria cyanescens in Italy - Mattia, Daniel; Mavica, Simone; Pietro, Chiara DI; Efstathiou, Styliana; Makris, Georgios; Kanetis, Loukas; Aiello, Dalia (My University, 2025)
Summary. Italy is the leading producer and the main exporting country of table grapes in the European Union. However, table grape production is affected by Grapevine Trunk Diseases (GTDs) which cause serious economic losses to grape growers. Aetiology of GTDs is crucial for application of effective management strategies, particularly regarding the quality of the grapevine propagation material. During 2022-23, four nurseries in Eastern Sicily, Southern Italy, were surveyed, and high incidence of propagation material with GTDs symptoms was found. Over 100 fungal isolates were collected from 80 symptomatic cuttings of ‘Italia’ and ‘Victoria’ cultivars grafted on rootstock 140RU. Of these isolates, 82 were molecularly analysed, and were found to belong to 22 genera. Isolation results highlighted the presence of well-known GTDs-related pathogens, including species within the Botryosphaeriaceae, and Phaeomoniella chlamydospora, Phaeoacremonium minimum, and Cylindrocarpon-like species. Less common fungi, including Neoscytalydium dimidiatum and Quambalaria cyanescens, were also isolated and characterized by molecular, morphological and phylogenetic analyses, and Koch’s postulates were fulfilled for these two species. This is the first study to associate N. dimidiatum and Q. cyanescens with table grape propagation material in Europe.
Keywords: isolate characterization; pathogenicity; Grapevine Trunk Diseases; nursery material